Student Science Process Skills through the Application of Computer Based Scaffolding assisted by PhET Simulation - Saputri, Affa Ardhi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2021)
Basic physics practicum learning through virtual laboratories is less than optimal in developing students' science process skills. This study reveals the results of improving students' science process skills based on the application of computer scaffolding assisted by PhET simulation. This study uses a quantitative approach with a sample of 14 students through purposive sampling technique. The research stages consist of introduction, implementation, and evaluation. Collecting data through interviews, tests, and observations. Data analysis using the N-gain test. The results showed an increase in students' science process skills on several indicators with various categories. The indicator is observing 0.49 (medium category), formulating hypotheses 0.34 (medium category), carrying out experiments 0.39 (medium category), data interpretation and analysis 0.42 (medium category), communicating 0.33 (medium category), and concluded 0.29 (low category). Computer-based scaffolding with PhET simulation is an online learning solution that can also be collaborated with offline learning to improve students' science process skills.